2020
DOI: 10.1007/s13205-020-02463-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological materials formed by Acidithiobacillus ferrooxidans and their potential applications

Abstract: A variety of biological materials including schwertmannite, jarosite, iron-sulfur cluster (ISC) and magnetosomes can be produced by Acidithiobacillus ferrooxidans (A. ferrooxidans). Their possible formation mechanisms involved in iron transformation, iron transport, and electron transfer were proposed. The schwertmannite formation usually occurs under the pH of 2.0-3.51, and a lower or higher pH will promote jarosite to be produced. Available Fe 2+ in the environment and the carrier proteins that can transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…Thus, Fe 3 O 4 nanoparticles coated with lipid bilayers possibly produced from many factories associated with the membrane in A. ferrooxidans BYM even though it does not contain MAI in the genome ( 23 , 72 ). Herein, on the basis of the findings in the present study and the results of previous research ( 23 , 40 ), we hypothesized that Fe 3 O 4 nanoparticle synthesis in A. ferrooxidans BYM is a complex sequential process mediated by several proteins ( Fig. 8 ).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Thus, Fe 3 O 4 nanoparticles coated with lipid bilayers possibly produced from many factories associated with the membrane in A. ferrooxidans BYM even though it does not contain MAI in the genome ( 23 , 72 ). Herein, on the basis of the findings in the present study and the results of previous research ( 23 , 40 ), we hypothesized that Fe 3 O 4 nanoparticle synthesis in A. ferrooxidans BYM is a complex sequential process mediated by several proteins ( Fig. 8 ).…”
Section: Discussionsupporting
confidence: 66%
“…S3). It has been reported that the formation of magnetic nanoparticles in A. ferrooxidans and MTB involved the uptake and transport of iron, the change of membrane structure, and oxidation-reduction process ( 40 ). The genome of A. ferrooxidans ATCC 23270 contains several open reading frames with high similarity to magnetosome genes of MTB, such as mpsA , mamE , mamB , and magA , which are associated with magnetosome membrane formation, oxidation-reduction process, iron transport, and iron uptake, respectively ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations